2017
DOI: 10.1085/jgp.201611683
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary insights into T-type Ca2+ channel structure, function, and ion selectivity from the Trichoplax adhaerens homologue

Abstract: The role of T-type calcium channels in animals without nervous systems is unknown. Smith et al. characterize TCav3 from Trichoplax adhaerens, finding expression in neurosecretory-like cells and preference for Ca2+ over Na+ via strong extracellular Ca2+ block, despite low selectivity for Ca2+ in the pore.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 113 publications
1
51
1
3
Order By: Relevance
“…Trichoplax also retains both homologues, but our mRNA expression and localization studies of RIMs and Ca V s point to low level expression (Figures 1 and S1), making it difficult to interpret their cell-type expression profiles and possible roles. We note that in ongoing studies being carried out in our lab, all three Trichoplax Ca V channels express in vitro to conduct voltage-sensitive Ca 2+ that resemble those of Ca V 1-Ca V 3 homologues from other animals ((Smith, et al 2017); unpublished data). However, the role of Ca V channels and transient membrane Ca 2+ signaling in Trichoplax biology is unknown.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Trichoplax also retains both homologues, but our mRNA expression and localization studies of RIMs and Ca V s point to low level expression (Figures 1 and S1), making it difficult to interpret their cell-type expression profiles and possible roles. We note that in ongoing studies being carried out in our lab, all three Trichoplax Ca V channels express in vitro to conduct voltage-sensitive Ca 2+ that resemble those of Ca V 1-Ca V 3 homologues from other animals ((Smith, et al 2017); unpublished data). However, the role of Ca V channels and transient membrane Ca 2+ signaling in Trichoplax biology is unknown.…”
Section: Discussionmentioning
confidence: 83%
“…The apparent absence of synapses in Trichoplax is not reflected by its expressed gene set, which in addition to RIM includes homologues for key active zone proteins such as SNARE and associated proteins, and scaffolding proteins that interact with Ca V 2 calcium channels at nerve terminals such as Mint, CASK, Liprin-α, ELKS and RIM-BP (Figure 1A and B). Trichoplax is also the most early-diverging animal with homologues for all three metazoan Ca V channel types: Ca V 1, Ca V 2 and Ca V 3 (Senatore, et al 2012; Moran and Zakon 2014; Senatore, et al 2016; Smith, et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, functional studies of distinct cell types, coupled with electrophysiology and/or optical recording, are a necessary next step in understanding the roles of electrical and calcium signaling in and play a major role in regulating cellular excitability. We found that despite its significant divergence at the amino acid sequence level, the Trichoplax Ca v 3 channel conducts low-voltage activated Ca 2+ currents with hallmark features for this channel type that are required for regulating excitability [108]. By extension, it is plausible that other and perhaps numerous Trichoplax ion channels share core functional attributes with their counterparts from other animals, which could be co-expressed in varying functional assemblages as occurs in neurons to produce alternate modalities of cellular excitation.…”
Section: Discussionmentioning
confidence: 92%
“…In Hydrozoan cnidarians, the nervous system is thought to be derived from I-cells that orginate in the endomesoderm (gastroderm) during embryonic development [89][90][91], although sensory cells can emerge from I-cell free animals [92,93]. In the absence of a true nervous (or musculature) system, neuropeptide and calcium signaling play a role in complex behaviors of these animals [94,95]. Our findings, although suggestive, require greater analysis and further study to truly understand how these and other developmental genes shape the body of Trichoplax.…”
Section: Discussionmentioning
confidence: 99%